Antibodies to human gastric epithelial cells and heat shock protein 60 in Helicobacter pylori positive mucosa associated lymphoid tissue lymphoma. Issue 1 (1st July 1999) - Kawahara, Y; Yokota, K; Mizuno, M; Yunoki, N; Uesu, T; Okada, H; Kobayashi, K; Hirai, Y; Oguma, K; Tsuji, T
Abstract : BACKGROUND: Development of gastric mucosa associated lymphoid tissue (MALT) lymphoma is thought to be closely associated with host immune reactions to Helicobacter pylori . AIM: To investigate humoral immune responses in patients with MALT lymphoma to antigens shared by H pylori and human gastric epithelial cells. METHODS: Sera were obtained from H pylori positive patients with MALT lymphoma (n = 11) or other gastroduodenal diseases (peptic ulcer, n = 40; non-ulcer dyspepsia, n = 20) and from H pylori negative healthy control subjects (n = 10). Antibodies to HGC-27 human gastric epithelial cells and human recombinant heat shock protein (Hsp) 60 were examined using an enzyme linked immunosorbent assay (ELISA) and immunoblotting. RESULTS: Antibody titres to HGC-27 cells were significantly elevated in H pylori positive patients with MALT lymphoma when compared with titres in patients with other gastroduodenal diseases and in healthy subjects. Immunoblotting of sera from patients with MALT lymphoma often detected a band with a molecular mass corresponding to Hsp60, and both ELISA and immunoblotting showed elevated antibody titres to the recombinant human Hsp60. Antigenic similarity between Hsp60 and H pylori HspB was documented by immunoblotting experiments. CONCLUSIONS: Autoantibodies reactive with host gastric epithelial cells are often increased in MALT lymphoma, and Hsp60 is a major target antigen. Immune responses induced by immunological cross reactivity between H pylori HspB and human Hsp60 in gastric epithelium may be involved in the development of MALT lymphoma.